Assessing Study Literacy and Tech Readiness in Medical Students: Kirkpatrick Model Evaluation : Menilai Kuliah Literasi Belajar dan Teknologi pada Mahasiswa Kedokteran: Evaluasi Model Kirkpatrick - Nugraheni, Elizabeth Sulastri (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
The ability to work with technology is essential for our future doctor. In the era of digitalization, doctor patient consultation is changing. Therefore, it is important for students to develop specific skills early in their medical education. To meet future competency demands and support sustainable learning, we designed 16 weeks The Learning Literacy and Technology course. Which is consists of soft-skills facilitation and technology and AI modules for the first semester medical students. This study used the Kirpatrick Four-Level of Evaluation Model to assess the impact of the course. This model is widely used to evaluate the program on four levels: Reaction, Learning, Behaviour, and Result. The aim of the study is to measure the evaluation outcome of this course in enhancing soft skills for learning and the use of technology in both medical education and future careers. A mixed method descriptive cross-sectional designs was used, incorporating quantitative data from the surveys and qualitative insights from guided interviews. Finding shows that quantiatively, students scored higher than 4 out of 5 across all levels. Qualitatively, similar themes emerged from the interview data. Overall, the mixed-method study indicates that the course effectively meets all four levels of the Kirkpatrick evaluation model.